(3TQM Yjhf GdMceIs - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3Gddge jG NGdb GdSehGJ hGdCQV hjG aGWQ GdSehGJ hGdCQV CeG HYO aEf cJGH Yjhf GdMceI CNHGQg SWQJ ai UMGFa GdeaGNQ s
(3BNQgG (B:s
(3hdeG PcQ Pdc NJe GdcJGH Hbhdg hGdMb hdi JSgjd SHdfG EdjgG Efg SejY eLjH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1186s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdadSaI hGdefWbs